DISTRIBUSI KLOROFIL-a PADA MUSIM TIMUR DI PERAIRAN SPERMONDE PROPINSI SULAWESI SELATAN - Abd. Rasyid J (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2011)
Clorophyl-a is one of Parameter that really determining primary productivity in thesea. Clorophyll-a data from MODIS AQUA/TERRA satellite that take from LAPAN (Lembaga Penerbangan dan Antariksa Nasional) in Pare-Pare about data from each week start from Oktober 2007-June 2009 (east season). According to the research result, we obtained an information that clorophyl-a consentration on season west washigh enough were is 0.15 – 1.15 mg/m3. High Clorophyll-a consentration is always near the island and beach area or coastal area due to the effect of nutrient supply that come from continent.